Tratamiento tributario de ingresos, gastos y su impacto en el estado de resultados integrales de las empresas PYMES - Villacís Baquero, Silvana Violeta (2023)
The objective of the investigation Tax Treatment of Income, Expenses and its Impact on the Statement of Comprehensive Income of SME Companies is to carry out a diagnosis of their tax situation, for which two companies that sell electrical appliances called Electro 1 and Electro 2 were considered, to demonstrate the affectation of non-deductible expenses, income exempt from income tax to the results, The methodology used was a mixed approach, quantitative information was used for the analysis of the financial statements, it was qualitative because interviews were carried out with counted experts and Observation of tax processes. The research is descriptive, explanatory and documentary to determine the tax treatment of income and expenses. The method used was inductive and analytical because income and expenses were analyzed, the impact of income and expenses on the EEFF was evaluated. It was possible to determine the lack of knowledge of the tax regulations and its incidence in the ERI, as a result of the investigation, a solution proposal was prepared, a Tax Treatment Model of Income and Expenses for SMEs [MTTIGPYMES] that will allow managers of the tax process in SMEs, adequately use current tax regulations, know the affectation of income and expenses on results, evaluate past, present and future tax risks, the need to strengthen internal tax control to avoid closure, bankruptcies, fraud, fines, and closure of companies.